Pendampingan Penulisan Essay Beasiswa S2 Pada Mahasiswa di Jurusan Aqidah dan Filsafat Islam IAIN Syekh Nurjati Cirebon - Saumantri, Theguh (Jurnal Makkareso, 2024)
In the era of higher education, community service activities have become an integral part of the university's mission in realizing the goals of the three pillars. The focus of community service on students at IAIN Syekh Nurjati Cirebon, particularly in mentoring the writing of S2 scholarship essays in the Department of Aqidah and Islamic Philosophy, highlights the importance of integrating academic learning with practical needs in the field. The purpose of this community service is to enhance students' skills and opportunities in writing S2 scholarship essays and to facilitate their understanding of the importance of essays in the scholarship application process. The method used in this activity is Participatory Learning and Action (PLA). This method aims to provide assistance to students in overcoming obstacles and meeting practical needs in essay writing. The conclusion of this mentoring activity shows that it underscores the importance of a good essay structure as a key to success in scholarship applications. A clear introduction, organized content, and a strong conclusion are essential components to be considered in writing scholarship essays. Furthermore, this mentoring activity demonstrates that through participatory approaches and effective guidance, students are able to improve their essay writing skills for scholarship preparation.